2018
DOI: 10.1016/j.clnu.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial to determine the impact of a digestion resistant starch composition on the gut microbiome in older and mid-age adults

Abstract: The 16S rRNA sequencing data and metadata generated in this study have been submitted to the NCBI Sequence Read Archive (SRA: http://www.ncbi.nlm.nih.gov/bioproject/381931).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
123
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 41 publications
16
123
2
Order By: Relevance
“…Proteins from Ruminococcaceae and Bacteriodiaceae were also increased in response to RS3. In agreement with our findings, previous studies have reported increases of bacteria from families Bifidobacteriaceae [11,12,[31][32][33], Ruminococcaceae [12,13,15,33], Eubacteriaceae [15,33,34], Lachnospiraceae [35] and Bacteriodiaceae [15,32] in response to different sources and forms of RS. Members of these bacterial families have been shown to be capable of metabolizing resistant starches [17,[36][37][38] due to their amylolytic activities [36,38], and many are butyrate producers [39].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Proteins from Ruminococcaceae and Bacteriodiaceae were also increased in response to RS3. In agreement with our findings, previous studies have reported increases of bacteria from families Bifidobacteriaceae [11,12,[31][32][33], Ruminococcaceae [12,13,15,33], Eubacteriaceae [15,33,34], Lachnospiraceae [35] and Bacteriodiaceae [15,32] in response to different sources and forms of RS. Members of these bacterial families have been shown to be capable of metabolizing resistant starches [17,[36][37][38] due to their amylolytic activities [36,38], and many are butyrate producers [39].…”
Section: Discussionsupporting
confidence: 93%
“…For example, fecal butyrate levels varied widely among 46 individuals given an RS dietary supplement [18]. In another study, MSPrebiotic (containing 70% RS2) increased SCFA levels in elderly adults but not mid-age adults, despite a significant increase in Bifidobacterium in both age groups [11]. Overall, the effects of RS on the microbiome appears to depend on the source and type of RS, and on individual variations in the human gut microbiomes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of a further seven studies reporting α‐diversity that were not included in the main meta‐analysis, two reported increases in diversity after the consumption of resistant starch type 2 (Alfa et al . ) and polydextrose (Costabile et al . ), with the remaining studies finding either no significant difference (for raffinose and resistant starch) (Fernando et al .…”
Section: Microbial Fermentation Of Fibrementioning
confidence: 99%
“…Based on six RCTs that reported data suitable for inclusion in the meta-analysis (investigating polydextrose, xylo-oligosaccharide, polysaccharopeptide, arabinoxylans and a high-fibre diet), fibre had no effect on a-diversity compared with control (So et al 2018). Of a further seven studies reporting a-diversity that were not included in the main meta-analysis, two reported increases in diversity after the consumption of resistant starch type 2 (Alfa et al 2018) and polydextrose (Costabile et al 2012), with the remaining studies finding either no significant difference (for raffinose and resistant starch) (Fernando et al 2010;Mart ınez et al 2010), conflicting results (for arabinoxylans) (Salden et al 2018) or not reporting group differences (for flaxseed mucilage) (Brahe et al 2015). The authors point out that this finding is inconsistent with observational studies that have reported a positive correlation between fibre intake and microbial diversity, when comparing populations from developed and developing countries (De Filippo et al 2010;Schnorr et al 2014) and may be explained by differing methodologies used for measuring diversity.…”
Section: Microbial Fermentation Of Fibrementioning
confidence: 99%